USING BODY DIAMENSION MEASURMENT AND THEIR RELATION IN PREDICTING WEIGHT IN IRAQI BUFFALOES - Radi Abdullah (Mesopotamia Journal of Agriculture)
This study was conducted on local buffalo in the area of Badosh region in ninava . The results revealed that: The overall means for body dimension (heart girth , belly girth , diagonal body length ,shoulder width , hip width , wither height and hip height) were 211.05 , 254.132 , 161.43 , 43.63 , 62.51 , 143.18 ,and 140.42 cm respectively. The age had a highly significant effect (p≤ 0.01)on the chest girth, diagonal body length and hip width and significant (p ≤ 0.05) on wither height with the increases in animal age, There was no significant effect on other dimensions. The diameter of the right front and left teats and those of the rear right and left treat were 2.9,3.6,3.11 and 3.37cm respectively. Advancing age of the animal had a highly significant effect (p ≤ 0.01) on teat diameter. The rear left teat diameter is greater than the front left teat about 0.31cm.and by also the diameter of the rear right teat was greater than the front right teat by 0.21cm. The distances between front and rear teats and between left front and left rear and between rear right and front right teats were 14.16,9.75,9.54.and 9.22cm.respeivectly.The distance between the front teat was greater than the rear one. Correlation values between body dimensions were positive and significan . Body weight can be predicted by using body dimensions measurements.